Vaccination for rheumatic diseases: Current issues (based on ACR guidelines) - B. S. Belov; N. V. Muravyeva; E. L. Nasonov (Научно-практическая ревматология, 2023)
In modern rheumatology, comorbid infections have a significant impact on morbidity and mortality, especially in immuno-inflammatory rheumatic diseases (IIRD). One of the ways to solve this problem is the study and active use of various vaccines. This article analyzes the recommendations for vaccination of patients with acute respiratory infections, proposed in 2022 by experts of the American College of Rheumatology (ACR). The safety and immunogenicity of vaccination associated with the prevention of various infections in patients with IVR are discussed. It is emphasized that the decision to suspend taking the drug before or after vaccination should be made taking into account the existing IIRD, its activity and the risk of vaccine-controlled infection. A key component of any vaccination strategy (especially for conditional recommendations) is decision-making together with the patient. The main directions of future research on the problem under consideration are outlined.